Avaliação de uma técnica para geração de modelos digitais de superfície utilizando múltiplas imagens - Oliveira, Raquel Alves De [UNESP]; Tommaselli, Antonio Maria Garcia [UNESP] (Universidade Federal do Paraná, 2014)
The efficient generation of digital surface model (DSM) from optical images has been explored for many years and the results are dependent on the project characteristics (image resolution, size of overlap between images, among others), of the image matching techniques and the computer capabilities for the image processing. The points generated from image matching have a direct impact on the quality of the DSM and, consequently, influence the need for the costly step of edition. This work aims at assessing experimentally a technique for DSM generation by matching of multiple images (two or more) simultaneously using the vertical line locus method (VLL). The experiments were performed with six images of the urban area of Presidente Prudente/SP, with a ground sample distance (GSD) of approximately 7cm. DSMs of a small area with homogeneous texture, repetitive pattern, moving objects including shadows and trees were generated to assess the quality of the developed procedure. This obtained DSM was compared to cloud points acquired by LASER (Light Amplification by Simulated Emission of Radiation) scanning as wells as with a DSM generated by Leica Photogrammetric Suite (LPS) software. The accomplished results showed that the MDS generated by the implemented technique has a geometric quality compatible with the reference models.

A utilização de imagens ópticas para a geração de Modelos Digitais de Superfície (MDSs) é explorada há muitos anos e os resultados dependem, além das características do projeto (resolução das imagens, tamanho da área de sobreposição entre as imagens, etc), das técnicas de correspondência de imagens aplicadas e da capacidade computacional para o processamento das imagens. Os pontos gerados com erros no processo de correspondência influenciam diretamente a qualidade dos produtos obtidos e, consequentemente, aumentam a necessidade da etapa onerosa de edição. O objetivo deste trabalho é a avaliação da técnica de geração de MDSs utilizando a correspondência simultânea entre múltiplas imagens pelo método de busca em linhas verticais (Vertical Line Locus-VLL). Nos experimentos foram utilizadas seis imagens da área urbana de Presidente Prudente-SP, com elemento de resolução aproximado de 7cm. Para análise da qualidade foram gerados MDSs de uma pequena área contendo áreas homogêneas, padrão repetitivo, objetos em movimento incluindo sombras e árvores grandes. O MDS obtido foi comparado com dados de varredura a LASER (Light Amplification by Simulated Emission of Radiation) e com o MDS gerado pelo software Leica Photogrammetric Suite (LPS). Os resultados mostraram a compatibilidade da qualidade entre os modelos gerados pela técnica implementada e os dados de referência.
Assessment of a technique for Digital Surface Model generation using multi images
Keywords: Modelo Digital de Superfície; Correspondência de Imagens; Busca em Linha Vertical; Digital Surface Models; Image Matching; Vertical Line Locus